2018
DOI: 10.1016/j.nicl.2017.10.028
|View full text |Cite
|
Sign up to set email alerts
|

An acute bout of aerobic or strength exercise specifically modifies circulating exerkine levels and neurocognitive functions in elderly individuals with mild cognitive impairment

Abstract: Although exercise is an effective way to decrease the risk of developing Alzheimer's disease, the biological basis for such benefits from the different exercise modes remains elusive. The present study thus aimed (i) to investigate the effects of acute aerobic or resistance exercise on neurocognitive performances and molecular markers when performing a cognitive task involving executive functioning in older adults with amnestic mild cognitive impairment (aMCI), and (ii) to explore relationships of acute exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
110
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(131 citation statements)
references
References 124 publications
(203 reference statements)
10
110
0
11
Order By: Relevance
“…The intensity-dependent increase in serum BDNF has also been positively associated with improved prefrontal cognitive functioning in humans (Hwang et al, 2016). Conversely, Tsai et al (2014Tsai et al ( , 2016Tsai et al ( , 2018 found no relationship between increased BDNF concentrations and improved cognitive performance following 30-min of moderateintensity exercise in both healthy adults and older adults with mild cognitive impairment. Accordingly, these results purport that the circulating BDNF response to exercise is not linked to post-exercise cognitive performance.…”
Section: Plasticity and Neurotrophic Factorsmentioning
confidence: 97%
See 1 more Smart Citation
“…The intensity-dependent increase in serum BDNF has also been positively associated with improved prefrontal cognitive functioning in humans (Hwang et al, 2016). Conversely, Tsai et al (2014Tsai et al ( , 2016Tsai et al ( , 2018 found no relationship between increased BDNF concentrations and improved cognitive performance following 30-min of moderateintensity exercise in both healthy adults and older adults with mild cognitive impairment. Accordingly, these results purport that the circulating BDNF response to exercise is not linked to post-exercise cognitive performance.…”
Section: Plasticity and Neurotrophic Factorsmentioning
confidence: 97%
“…The transient increase in BDNF after acute exercise may explain the lack of correlations with cognitive performance. Therefore, it is possible that the post-exercise timing of the serum BDNF measurements align with the cognitive testing influenced outcomes (Tsai et al, 2018). Alternately, non-BDNF mechanisms (neurotrophins, arousal, hormones) could be responsible for the cognitive changes after exercise.…”
Section: Plasticity and Neurotrophic Factorsmentioning
confidence: 99%
“…Esto puede deberse al hecho que los tratamientos focales requerirían de un nivel de intensidad entre moderado y vigoroso (Borg, 1970) para hallar resultados favorables. Debido a la exigencia que dichas prácticas representan a nivel corporal, y a fin de salvaguardar la salud de los individuos, las investigaciones que cuentan con la participación de AM realizan una selección exhaustiva y minuciosa de la muestra (Kimura & Hozumi, 2012;Tsai et al, 2018). Por ello, hallar una muestra representativa que al mismo tiempo cumpla con todos los requisitos en cuanto a la salubridad esperada, puede resultar una tarea ardua.…”
Section: Intervenciones Focalesunclassified
“…En línea con estos resultados, un trabajo empleó una metodología similar, pero adicionando un grupo de ejercicio no aeróbico de fuerza muscular como tercer tratamiento y evaluando la inhibición cognitiva. Se halló un mejor desempeño en ambos grupos activos en comparación al grupo control(Tsai, Ukropec, Ukropcová, & Pai, 2018). A pesar de los efectos favorables observados mediante las dosis agudas, los autores proponen estudios complementarios, adicionando entrenamientos repetitivos y sostenidos en el tiempo como variable comparativa.…”
unclassified
See 1 more Smart Citation